2020
DOI: 10.3390/polym12092070
|View full text |Cite
|
Sign up to set email alerts
|

How Is Rheology Involved in 3D Printing of Phase-Separated PVC-Acrylate Copolymers Obtained by Free Radical Polymerization

Abstract: New auto-plasticised copolymers of poly(vinyl chloride)-r-(acrylate) and polyvinylchloride, obtained by radical polymerization, are investigated to analyse their capacity to be processed by 3D printing. The specific microstructure of the copolymers gives rise to a phase-separated morphology constituted by poly(vinyl chloride) (PVC) domains dispersed in a continuous phase of acrylate-vinyl chloride copolymer. The analysis of the rheological results allows the suitability of these copolymers to be assessed for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, molecular interpretation of the results in terms of chain stretch and extent of disentanglement was not provided. Along similar lines, Peñas et al investigated the extrusion based AM of PVC/acrylate copolymers and found filament buckling to be a serious issue in FFF of the material . However, the polymer was still printable using a screw-based extrusion system and the associated viscoelastic and rheological characteristics to ensure interlayer welding was studied.…”
Section: Importance Of Polymer Rheology In Materials Extrusion Based Ammentioning
confidence: 99%
“…However, molecular interpretation of the results in terms of chain stretch and extent of disentanglement was not provided. Along similar lines, Peñas et al investigated the extrusion based AM of PVC/acrylate copolymers and found filament buckling to be a serious issue in FFF of the material . However, the polymer was still printable using a screw-based extrusion system and the associated viscoelastic and rheological characteristics to ensure interlayer welding was studied.…”
Section: Importance Of Polymer Rheology In Materials Extrusion Based Ammentioning
confidence: 99%
“…In the last 25 years, a number of Spanish papers [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] have dealt with viscosity results of polymer melts related to their aptness for extrusion moulding. The article of Vega et al [ 7 ], the result of the collaboration between the University of the Basque Country and REPSOL, is the most cited among the Spanish papers properly focused on the rheology applied to polymer processing, according to the Web of Science.…”
Section: Thermoplastic Polymersmentioning
confidence: 99%
“…Spanish rheologists have worked on the melt fracture of polypropylene [ 22 ], poly(styrene-ethylene/buthylene-styrene) triblock copolymers [ 24 ], and poly(vinyl chloride) (PVC) [ 31 ]. As a matter of fact, research on the rheology of PVC processing has gained a certain reputation thanks to the collaboration between the Spanish company ERCROS and the Rheology group of the University of the Basque Country [ 14 , 15 , 19 , 32 , 33 , 34 , 35 ]. The most recent of these papers focuses on the rheology applied to additive manufacturing, which is treated in Section 2.3 .…”
Section: Thermoplastic Polymersmentioning
confidence: 99%
See 2 more Smart Citations